Synthesis and characterization of New Dithiophosphonate Ligands - SAĞLAM, ERTUĞRUL GAZİ (My University, 2023)
Perthiophosphonic acid anhydrides (PTPA) are used as a starting agent in the synthesis of phosphorus-sulfur compounds[1].These derivatives can be classified into dithiophosphates, dithiophosphinates and dithiophosphonates (DTPOA). In this survey, we synthesized new DTPOAs starting from PTPAs formerly synthesized by us ADDIN EN.CITE <EndNote><Author>Bulat</Author><Year>2022</Year><RecNum>32</RecNum><DisplayText>[32]</DisplayText><record><rec-number>32</rec-number><foreign-keys><key app="EN" db-id="2dt9vd0elr9x03eza0rp0z28z2tsap2p2t9p" timestamp="1670249129">32</key></foreign-keys><ref-type name="Journal Article">17</ref-type><contributors><authors><author>Bulat, Elif</author><author>Sağlam, Ertuğrul Gazi</author><author>Zeyrek, Celal Tuğrul</author><author>Akkoç, Senem</author><author>Zorlu, Yunus</author><author>Dal, Hakan</author></authors></contributors><titles> Ni(II) complexes with 1,3,2,4-dithiadiphosphetane 2,4-disulfide-based ligands: Structural insights, theoretical studies, and anticancer activities <secondary-title>Applied Organometallic Chemistry</secondary-title></titles><periodical><full-title>Applied Organometallic Chemistry</full-title></periodical><pages>e6821</pages><volume>36</volume><number>10</number><dates><year>2022</year></dates><isbn>0268-2605</isbn><urls><related-urls>https://onlinelibrary.wiley.com/doi/abs/10.1002/aoc.6821</related-urls></urls><electronic-resource-num>https://doi.org/10.1002/aoc.6821</electronic-resource-num></record></EndNote>[2,3]. In other words, new dithiophosphonic acids (HS2P((2,4-CH3O)2-C6H3)(ORn), HLx,y; RX1=n-propyl-, RX2=2-butyl-,Ry=methyl- were synthesized by reacting of 2,4-bis(3,4-dimethoxyphenyl)-1,3-dithia-2,4-diphosphetane 2,4-disulfide, (SAV-A1) and 2,4-bis(2,4-dimethoxyphenyl)-1,3-dithia-2,4-diphosphetane 2,4-disulfide, (SAV-A2) with aliphatic alcohols. All DTPOAs were transformed to relating to ammonium salts, [NH4Lx,y] (Scheme 1).
Keywords: Kimya; İnorganik Kimya; Temel Bilimler; Chemistry; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; KİMYA, İNORGANİK VE NÜKLEER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; CHEMISTRY; MULTIDISCIPLINARY SCIENCES; CHEMISTRY, INORGANIC & NUCLEAR; İnorganik kimya; Kimya (çeşitli); Genel Kimya; Multidisipliner; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Multidisciplinary; Physical Sciences